Ecological momentary assessment of affective and interpersonal instability in adolescent non-suicidal self-injury - Santangelo, Philip S.; Koenig, Julian; Parzer, Peter; Resch, Franz; Kaess, Michael (Journal of abnormal child psychology, 2017)
Affective and interpersonal instability, both core features of Borderline Personality Disorder (BPD), have been suggested to underlie non-suicidal self-injury (NSSI). Ecological momentary assessment (EMA) is the method of choice when investigating dynamic processes. Previously no study addressed affective and interpersonal instability in daily life of adolescents engaging in NSSI. Female adolescents with NSSI (n = 26) and age- and sex-matched healthy controls (n = 20) carried e-diaries on 2 consecutive weekends and were prompted in hourly intervals to rate their momentary affective state and feelings of attachment towards their mother and best friend. The majority of participants in the NSSI group also fulfilled diagnostic criteria for BPD (73%). Squared successive differences were calculated to quantify instability. Adolescents with NSSI reported less positive affect, t (44) = 6.94, p < 0.01, lower levels of attachment to the mother, t (44) = 5.53, p < 0.01, and best friend, t (44) = 4.36, p < 0.01. Both affective, t (44) = −5.55, p < 0.01, and interpersonal instability, mother: t (44) = −4.10, p < 0.01; best friend: t (44) = −4.57, p < 0.01, were significantly greater in adolescents engaging in NSSI. In the NSSI group, the number of BPD criteria met was positively correlated with affective instability, r = 0.40, p < 0.05, and instability of attachment to the best friend, r = 0.42, p < 0.05, but not instability of attachment towards the mother, r = 0.06, p = 0.79. In line with previous work in adults, NSSI is associated with affective and interpersonal instability assessed by EMA in adolescents. Preliminary findings highlight the association of affective and interpersonal instability with diagnostic criteria for BPD. Clinical implications and avenues for further research are discussed.